Ann Beattie’nin “Kar” Adlı Kısa Kısa Hikayesinde Soğuk İmgelemin Yansıtılması - Köseman, Zennure (Fırat University, 2019)
Bu makale, doğal çevrede imgelerin ve sembollerin insanın iç dünyasını Ann Beattie’nin “Kar” adlı kısa kısa hikayesinde olduğu vurgulamayı amaçlamaktadır. Orman benzeri bir mekanın derinliklerinde, soğukluk, iki sevgiliyi huzur olma ve dinlenme için çekmektedir. Kullanılan dil bu soğuk havayı hissettirir. Hikayenin sonunda, kar küreme aracı orada yaşayan insanların iç dünyasındaki karanlıkları temizlercesine karı temizlemektedir. Kullanılan dilde saklanan sırlar varmışcasına şairane bir anlatım vardır. Erkek sevgili, arkadan “Neden böyle oldu?” sorularını bırakarak isimsiz kadını birden terk eder. Yaşanılan ev, sadece üç şey barındırarak saklanılan mesajları yansıtır: bir kütüphane, şömine, ve duvar kağıdı. Kar, kar küreme aracı, şömine bir bütün olarak açık uçlu kısa kısa hikayenin içerisinde derinlerde şiirsel mesajları yansıtmaktadır.

This article intends to highlight how the usage of images and symbols reflect the inner psyche of individuals in the natural setting as in Ann Beattie’s “Snow.” The coldness in the depths of the forest like setting pulls two lovers to the landscape to have a rest and happiness. The language spent sounds all the coldness. At the end, the snowplow scraps all the snow outside as if cleaning the darkness of the inner psyches of individuals living there. The language used is poetic enough to keep all the secrets in itself. The male lover abruptly leaves the female lover by creating the questions to find the reasons for departing. The house they accomodate reflects all the hidden messages having solely three belongings: a library, a fireplace and a wallpaper. The snow, snowplow, ice, cold water, fireplace sound coldness as a whole in the context of the open-ended short short story which reflects poetic messages in depth.
THE REFLECTION OF THE IMAGERY OF COLDNESS IN ANN BEATTIE’S “SNOW”